2014
DOI: 10.3109/02652048.2014.918666
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of ursodeoxycholic acid nanoparticles in animal model of inflammatory bowel disease

Abstract: This study presents the improved efficacy of UNPs in animal model of IBD due to complete release of drug at the desired site of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…13,115,116 Several formulations of UDCA have been developed to try to increase colonic delivery, including conjugation with glutamate, nanosuspensions/nanoparticles, and microbial derivation. [116][117][118] The UDCA-glutamate prevents absorption and biotransformation in the small intestine but takes advantage of the peptide bond cleavage within the colonic brush boarder enzymes to remove the glutamate thus allowing for colonic delivery of UDCA. 116 UDCA nanosuspensions encapsulate this bile acid and allow for increased colonic transit time.…”
Section: Ursodeoxycholic Acid Modulation Of Microbiota-bile Acid-hostmentioning
confidence: 99%
See 1 more Smart Citation
“…13,115,116 Several formulations of UDCA have been developed to try to increase colonic delivery, including conjugation with glutamate, nanosuspensions/nanoparticles, and microbial derivation. [116][117][118] The UDCA-glutamate prevents absorption and biotransformation in the small intestine but takes advantage of the peptide bond cleavage within the colonic brush boarder enzymes to remove the glutamate thus allowing for colonic delivery of UDCA. 116 UDCA nanosuspensions encapsulate this bile acid and allow for increased colonic transit time.…”
Section: Ursodeoxycholic Acid Modulation Of Microbiota-bile Acid-hostmentioning
confidence: 99%
“…116 UDCA nanosuspensions encapsulate this bile acid and allow for increased colonic transit time. 117,118 UDCA could also be microbially derived from administration of UDCA-producing bacteria, such as Clostridium baratii or Ruminococcus gnavus N53 (Figure 3). 61,90 Additional research is required to investigate the use of UDCA-producing bacteria in vivo.…”
Section: Ursodeoxycholic Acid Modulation Of Microbiota-bile Acid-hostmentioning
confidence: 99%
“…The biological actions of UDCA have been mostly studied in the liver, where it has been shown to have immunomodulatory and anti-apoptotic effects, and to prevent cytokine release from hepatocytes (1,34,36). Interestingly, several studies have shown that UDCA also exerts protective actions in animal models of intestinal inflammation, effects which were associated with reduced levels of mucosal cytokines, nitric oxide, and prevention of epithelial apoptosis (8,22,23,28).…”
Section: Il-8 Pg/mlmentioning
confidence: 99%
“…Проводится экспериментальное исследование на животных моделях УДХК в виде поликатионных наночастиц (UNPs), что возможно сможет повысить эффективность препарата. Так же продолжается активное изучение профилактическое применение новых производных УДХК, например нор-УДХК, таурохолевой кислоты [21][22][23].…”
Section: клинико-патогенетическое обоснование «гепатопротекции сопровunclassified